Steady State Optimal Load Shedding Using Particle Swarm Optimization - Nepal, Ujjwal; Rawal, Tapendra; Nayak, Rohan; Chaudhary, Jyoti; Malla, Tanus Bikram (Journal of Science and Engineering, 2025)
Power systems experience active and reactive power shortages when a significant plant fails to generate power. It is essential to maintain a supply-demand balance when there is no alternative to bring power from a tie line grid other than the power source available. Otherwise, the system may face under-voltage and under-frequency, leading to cascading failure to eventual blackout. Load shedding is a crucial strategy to maintain supply-demand balance to mitigate such problems. The traditional method of load shedding failed to leverage an optimized approach, leading to suboptimal performance. This study investigates optimized load shedding that uses the Particle Swarm Optimization algorithm to shed load optimally and allocate available power, adhering to system operational constraints. The IEEE 14 bus test system is used for the study, where the generational loss case is explored. Simulation results demonstrated that, for 26.20% of the generational deficit, the proposed approach was able to shed 67.62 MW of total load, improving the voltage profile of load buses. The applied method is compared with the existing heuristic-IHS method to validate the findings.